Strategic Management 2 - Partridge Lesley (Financial Times Management, 1999)
Designed by some of the world's leading experts and regularly updated, the materials combine academic excellence with day-to-day pragmatism resulting in one of the most practical and stimulating ranges available. Introduction to Workbook 2, Strategic Options, Generic Competitive Strategies, Product/ Market Growth Strategies, Linking Strategic Options to SWOT, Methods of Development, Evaluation and Selection, Gap Analysis, Criteria for Evaluation, Selecting Strategic Options, Making a Case, Implementing Strategy, The Implementation Process, Aligning People Behind Your Strategy, Creating a Culture for Success, Working in the Organizational Structure, Planning Implementation, Balanced Scorecard, Managing Strategic Change, What is Strategic Change?, Pressures for Strategic Change, Forces for and Against Change, Responses to Change, Change Management Roles, Planned Approaches to Managing Change, The Choice Management - Change Management Model, Further Reading, References.